Ézéchiel 18 et les défis que comporte l’analyse de l’exégèse intra-biblique - Maurais, Jean (Vetus Testamentum, 2015)
The relationship between Ezekiel 18:1-4 and Exodus 20:5-6 is sometimes interpreted in a way that highlights three difficulties encountered by modern exegetes when assessing the motivations underlying inner-biblical exegesis. From these three difficulties emerges another explanation of Ezekiel’s intention which illustrates some principles that could help refine the analysis of inner-biblical exegesis.